1983
DOI: 10.1021/ma00236a022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mobilities of individual constituent carbons of solid polyesters above Tg as studied by carbon-13 nuclear magnetic resonance spectroscopy

Abstract: High-resolution 13C spectra and spin-lattice relaxation times Tl have been measured for solid terephthalic acid polyesters [-COC6HlC00(CH2),0-].(m = 2, 3,4, 6, and 10) and succinic acid polyesters , (m = 2 and 4) over a wide range of temperatures above Tp by the 'H scalar-decoupling technique. The high-resolution lines of the individual carbons of the terephthalic acid polyesters appear a t different temperatures, T,, indicating that the carbons differ greatly in molecular mobility. According to the results, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Horii et al 21 and Mori et al 22 have investigated on the segmental motions of aromatic polyesters containing terephtahloyl and naphthaloyl residues, respectively, using 13 C nuclear magnetic resonance spectroscopy. According to their results, butylene unit is more flexible than the ethylene unit in these aromatic polyesters so that the high chain mobility of PBN may give a faster crystallization rate, 22 and the butylene sequence may be the smallest unit of independent inner motions of the CH 2 sequence in these analogous aromatic polyesters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horii et al 21 and Mori et al 22 have investigated on the segmental motions of aromatic polyesters containing terephtahloyl and naphthaloyl residues, respectively, using 13 C nuclear magnetic resonance spectroscopy. According to their results, butylene unit is more flexible than the ethylene unit in these aromatic polyesters so that the high chain mobility of PBN may give a faster crystallization rate, 22 and the butylene sequence may be the smallest unit of independent inner motions of the CH 2 sequence in these analogous aromatic polyesters.…”
Section: Resultsmentioning
confidence: 99%
“…According to their results, butylene unit is more flexible than the ethylene unit in these aromatic polyesters so that the high chain mobility of PBN may give a faster crystallization rate, 22 and the butylene sequence may be the smallest unit of independent inner motions of the CH 2 sequence in these analogous aromatic polyesters. 21 This chemical structure difference should also give rise to the differences in the amount of intermolecular hydrogen bonding interactions when these aromatic polyesters are blended with PVPh. The ester C = O groups of both PEN and PTN can be thought of as dynamically restricted due to the limited mobility for the ethylene and trimethylene units that will not allow the facile orientation of the C = O groups to the PVPh hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of PBS have been extensively investigated in the literature using different experimental techniques: X-ray diffraction, electron microscopy, and C NMR [ 63 , 64 , 65 , 66 ]. PBS has two crystalline forms: α and β.…”
Section: Thermal Morphological and Mechanical Propertiesmentioning
confidence: 99%
“…loc~ is small (the smallest among the three polymers studied) for the following reasons. It is well known that PET is a hydrophobic polymer; its melting point is 270 ~ [29] and the segmental motion of the polymer chain, in the dry state, only initiates around 120 ~ as revealed by Kitamaru and coworkers by the high-resolution 13C NMR (nuclear magnetic resonance) spectroscopy [30]. In the swollen state, as is the case in the present study, however, it is reported [31] that the presence of water shifts Tg of PET to a lower temperature by ca.…”
Section: Diffusion Ofpna In Petat 100 ~ C From the Buoh/h E 0 Mixed Smentioning
confidence: 99%